Environmental agreement under the non-interference principle: the case of ASEAN agreement on transboundary haze pollution - Fikri Muhammad (International Environmental Agreements: Politics, Law and Economics, 2021)
It is widely understood that the environmental problem is getting borderless and challenging, requiring concerted efforts of many states and increasing the need for international agreements. However, only for the agreement to exist may not be sufficient—the agreement needs to be credible: obliging the signatories with actions associated with the goal, displaying clear and unambiguous rules, and involving third parties in the dispute settlement. Unfortunately, in the presence of the non-interference principle, the creation of a credible agreement may be implausible as, conceptually, the principle is innately antipodal to hard obligations and third-party involvement in the dispute settlement. This case study seeks to understand how the legalization of the ASEAN Agreement of Transboundary Haze Pollution conformed to the non-interference principle and influenced Indonesia, the main laggard, in dealing with the predicament accordingly. Diverging with the common understanding, the agreement seems to carry strong obligation and precision, as shown in the main agreement and its protocols. However, the apparent downside lies in the lack of delegation dimension, as the current dispute resolution is made through diplomatic efforts that led to fruitless outcomes. This study counters the simplistic view of the association between the non-interference principle and the lack of obligations. Overall, this study points out the importance of the delegation dimension in regionalization and encourages the interventionist approach concerning global environmental protection.
Keywords: 330; Legalization; Non-interference principle; Hard law; Transboundary haze; ASEAN